The influence of synthesis parameters on swelling behaviour of pH-sensitive acrylate based hydrogels - Simendić Jaroslava Budinski; Suzana Cakić (Zaštita Materijala)
In this work poly(acrylamide-co-acrylic acid) based hydrogels were prepared using the two types of initiators - potassium persulfate (KPS) and ammonium persulfate (APS) and accelerator N,N,N’,N’-tetramethylethylenediamine (TEMED). N,N’-methylenebis(acrylamide) (MBAM) was used as crosslinking agent (1 and 3% per total weight of monomers). For the synthesis of hydrogels, acrylic acid (Aac) and acrylamide (Aam) were used in the following mass ratios: 30:70, 50:50, 70:30 and 0:100% Aac/Aam. The swelling behaviour of cross-linked copolymers was characterized in acidic (pH=4.5) and alkaline (pH=10) medium at constant temperature of 37°C. Lower amount of crosslinking agent has given the hydrogels with greater water absorption capacity. The forming of polymer network has been confirmed by FT-IR method. Thermal properties of obtained hydrogels were analyzed by differential scanning calorimetry (DSC). Obtained results have showed the strong correlation between hydrogels composition and their swelling and thermal properties.